2021
DOI: 10.3389/fgene.2021.758394
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and Indicine Haplotype Representation in Advanced Generation Individuals From Three American Breeds

Abstract: Development of the American Breeds of beef cattle began in the 1920s as breeders and U. S. Experiment Station researchers began to create Bos taurus taurus × Bos taurus indicus hybrids using Brahman as the B. t. indicus source. By 1954, U.S. Breed Associations had been formed for Brangus (5/8 Angus × 3/8 Brahman), Beefmaster (½ Brahman × ¼ Shorthorn × ¼ Hereford), and Santa Gertrudis (5/8 Shorthorn × 3/8 Brahman). While these breeds were developed using mating designs expected to create base generation animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 156 publications
(76 reference statements)
3
4
1
Order By: Relevance
“…The local ancestry results showed that BTA5 has a candidate region almost completely selected towards Zebuine. This is concordant with previous results that reported higher Zebuine proportions than expected in BTA5 (Crum et al, 2021; Paim et al, 2020b; Porto‐Neto et al, 2014). Furthermore, a signature of selection in this region was previously identified by Porto‐Neto et al (2014), who reported a region of 20 Mb under selection in Tropical Composite cattle from Australia that affects several productive traits (parasite resistance, yearling weight, body condition score, coat colour, etc.).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The local ancestry results showed that BTA5 has a candidate region almost completely selected towards Zebuine. This is concordant with previous results that reported higher Zebuine proportions than expected in BTA5 (Crum et al, 2021; Paim et al, 2020b; Porto‐Neto et al, 2014). Furthermore, a signature of selection in this region was previously identified by Porto‐Neto et al (2014), who reported a region of 20 Mb under selection in Tropical Composite cattle from Australia that affects several productive traits (parasite resistance, yearling weight, body condition score, coat colour, etc.).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are quite similar to those reported by Goszczynski et al (2018) in a smaller sample size, where the average Angus fraction was 63.7%. This also agrees with those reported by Paim et al (2020b) and Crum et al (2021), who observed a higher proportion of Angus (74.19% and 72.40%, respectively) in the USA compared with expectations. However, the initial difference in Taurine composition between USA and Argentinean Brangus (resulting from the selection criteria applied by the USA and Argentinean associations) could have been maintained in time due to the low percentage (<5%) of foreign semen (mostly from the US) in the Argentinean breed.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations